Synthesis of Indoxyl-glycosides for Detection of Glycosidase Activities - Böttcher, Stephan (J Vis Exp, 2015)
Indoxyl glycosides proved to be valuable and versatile tools for monitoring glycosidase activities. Indoxyls are released by enzymatic hydrolysis and are rapidly oxidized, for example by atmospheric oxygen, to indigo type dyes. This reaction enables fast and easy screening in vivo without isolation or purification of enzymes, as well as rapid tests on agar plates or in solution (e.g., blue-white screening, micro-wells) and is used in biochemistry, histochemistry, bacteriology and molecular biology. Unfortunately the synthesis of such substrates proved to be difficult, due to various side reactions and the low reactivity of the indoxyl hydroxyl function. Especially for glucose type structures low yields were observed. Our novel approach employs indoxylic acid ester as key intermediates. Indoxylic acid esters with varied substitution patterns were prepared on scalable pathways. Phase transfer glycosylations with those acceptors and peracetylated glycosyl halides can be performed under common conditions in high yields. Ester cleavage and subsequent mild silver mediated glycosylation yields the peracetylated indoxyl glycosides in high yields. Finally deprotection is performed according to Zemplén.